2017
DOI: 10.5056/jnm16165
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of the Eating Assessment Tool-10 to Detect Aspiration in Patients With Neurological Disorders

Abstract: Background/AimsDysphagia is common in patients with neurological disorders. There is a need to identify patients at risk early by a useful clinical tool to prevent its serious complications. The study aims to determine the ability of the Turkish version of Eating Assessment Tool-10 (T-EAT-10) to detect aspiration in patients with neurological disorders. MethodsTwo hundred fifty-nine patients with neurological disorders who had complaints about swallowing difficulty and referred for a swallowing evaluation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
0
19
0
3
Order By: Relevance
“…It includes 10 questions, with a maximum total score of 40 points; a score equal or greater than 3 points suggests a potential swallowing problem [11,12]. Furthermore, Arslan et al [13] investigated the ability of EAT-10 to detect aspiration in a group of neurological patients with different diagnoses, demonstrating that it can be safely used to screen patients with neurologic disorders who are at risk of unsafe airway protection or potentially with OD.…”
Section: Introductionmentioning
confidence: 99%
“…It includes 10 questions, with a maximum total score of 40 points; a score equal or greater than 3 points suggests a potential swallowing problem [11,12]. Furthermore, Arslan et al [13] investigated the ability of EAT-10 to detect aspiration in a group of neurological patients with different diagnoses, demonstrating that it can be safely used to screen patients with neurologic disorders who are at risk of unsafe airway protection or potentially with OD.…”
Section: Introductionmentioning
confidence: 99%
“…A study used the Turkish EAT-10 to detect aspiration in patients with various neurological disorders (n=259) including MS (n=24) and stroke (n=118) and found it useful to identify dysphagia patients with unsafe airway protection. 25 A previous study with a large sample of patients with dysphagia (N=360) found the EAT-10 is able to predict aspiration risk with the sensitivity of 71% when the EAT-10 score is greater than 15, and patients with EAT-10 score > 15 are 2.2 times more at risk of aspiration. 26 The readability of EAT-10 has been also demonstrated that supports its use in neurological conditions with dysphagia including MS. 27 To investigate the reliability and validity of the Turkish DYMUS in patients with MS (n=117), significant correlations were revealed between the DYMUS and EAT-10 (r = 0.90, p<0.001).…”
Section: Eating Assessment Tool (Eat-10)mentioning
confidence: 95%
“…18 The EAT-10 questionnaire has been crossculturally adapted and validated to different languages. [19][20][21][22][23][24][25][26][27] The EAT-10 questionnaire assesses the body function, activity, and participation of the swallowing. A study used the Turkish EAT-10 to detect aspiration in patients with various neurological disorders (n=259) including MS (n=24) and stroke (n=118) and found it useful to identify dysphagia patients with unsafe airway protection.…”
Section: Eating Assessment Tool (Eat-10)mentioning
confidence: 99%
“…Anxiety is most commonly linked with intermittent dysphagia while depression is most often seen with progressive dysphagia (Eslick & Talley, 2008). Strategies like selecting foods that they can manage and will enjoy as well as having to take additional time to eat a meal can reduce the patient's overall desire to eat when they experience difficulty or embarrassment with using these compensations to safely swallow (Arslan, Demir, Kilinc, & Karaduman, 2017).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Having tests that can quickly, reliably, and validly screen patients for dysphagia, including the severity, allows for treatments to begin sooner, making it possible to prevent some of the more dangerous complications 7 like dehydration and malnutrition (Arslan et al, 2017). Nguyen et al (2005) found the level of dysphagia severity to be statistically significant in respect to its effect on patient quality of life (Nguyen et al, 2005).…”
Section: Quality Of Lifementioning
confidence: 99%